Preferences for Redistribution and International Migration - Ilpo Kauppinen; Panu Poutvaara (ifo Institute - Leibniz Institute for Economic Research at the University of Munich, 2019)
The Tiebout hypothesis suggests that people who migrate from more to less redistributive countries are more negative towards redistribution than non-migrants. However, differences between migrants' and non-migrants' redistributive preferences might also reflect self-interest. We present a model in-corporating these competing mechanisms and test it using survey data on Danish emigrants and non-migrants. We find strong support for the Tiebout hypothesis among men, while women's preference patterns are opposite to what the hypothesis predicts. Even though emigrants neither pay taxes nor receive benefits in their country of origin, they tend to support policies that would be beneficial for people like themselves.
Keywords: D64; D72; F22; J61; H20; 330; Migration; emigration; welfare state; redistribution; political preferences